THE RELATIONSHIP BETWEEN NUTRITION KNOWLEDGE AND MOTHERS’ BEHAVIOUR IN PROCESSING FOOD AT BANGGAI ISLAND, CENTRAL SULAWESI - Laurensi Sasube; Aldian Hein Luntungan (LPPM Universitas Dhyana Pura, 2018)
ABSTRACTThe skills of mothers in processing healthy food determines the quality of children's nutritional intake. In addition, nutritional knowledge is sufficient to play a role in producing maternal skills in processing food. This study aims to analyze the relationship between the level of mother’s knowledge and skills in processing healthy food in Banggai Islands, Central Sulawesi. This type of this research is cross sectional. The level of mother's knowledge and skills in processing healthy food is obtained from the questionnaires distributed. The relationship between the two variables was seen based on the correlation test. The results showed that 76.6% had a level of knowledge that was still lacking in nutrition, where 14.9% had a enough level of nutrition knowledge and the other 8.5% have a good level of knowledge, and besides, mothers with healthy food processing skills have quite a lot of quantity with 63.8% of them who always use fresh ingredients in processing food. The results of this study indicate that there is no correlation between the level of maternal knowledge and maternal skills in processing healthy food on Banggai Island, Central Sulawesi (p>0,05)Keywords: mothers’ nutrition knowledge, behaviour , processing foodABSTRAKKeterampilan ibu dalam mengolah makanan yang sehat mendeterminasi kualitas asupan gizi anak. Disamping itu, pengetahuan gizi yang bai berperan dalakm menghasilkan keterampilan ibu dalam mengolah makanan. Penelitian ini bertujuan untuk menganalisis hubungan antara tingkat pengetahuan ibu dan keterampilan dalam mengolah makanan yang sehat di kepulauan Banggai, Sulawesi tengah. Jenis penelitian ini yaitu cross sectional. Tingkat pengetahuan ibu dan keterampilan mengolah makanan sehat diperoleh dari kuisioner yang dibagikan. Hubungan antara kedua variable dilihat berdasarkan uji korelasi. Hasil penelitian menunjukkan bahwa sebanyak 76.6% memiliki tingkat pengetahuan gizi kurang, dimana 14,9% memiliki tingkat pengetahuan gizi yang cukup dan 8,5% lainnya memilki tingkat pengetahuan gizi yang baik. Ibu dengan keterampilan mengolah makanan yang sehat memiliki kuantitas yang cukup banyak yaitu 63,8%, diantaranya yang selalu menggunakan bahan segar dalam mengolah makanan. Hasil penelitian ini menunjukkan bahwa tidak ada hubungan antara tingkat pengetahuan gizi ibu dengan keterampilan ibu dalam mengolah makanan yang sehat di pulau Banggai, Sulawesi Tengah (p>0,05)Kata kunci: pengetahuan gizi ibu, perilaku, pengolahan makanan